Phytate degradation and pre-cecal phosphorus digestibility of raw vs. crimped-ensiled faba beans (Vicia faba L.) fed to broiler chickens - Soares, Letícia; Högel, Heidi; Keto, Liisa; Franco, Marcia; Rinne, Marketta; Rodehutscord, Markus; Viana, Gabriel da Silva (Elsevier, 2026)
The current study was conducted to determine the effects of crimping and ensiling process on the pre-cecal disappearance of myo-inositol hexakisphosphate (InsP6) and the pre-cecal digestibility (pcd) of total phosphorus (P) of faba bean seeds (cv. Vire) fed to broiler chickens. On d 21 post-hatch, 360 male Ross308® broiler chicks were randomly assigned to one of six treatments, each with six replicates of 10 chicks, for a 7-day assay. The experimental treatments consisted of six diets (mash) containing either raw [5.5 g P/kg dry matter (DM); 9.37 g InsP6/kg DM] or crimped-ensiled (5.7 g P/kg DM; 8.45 g InsP6/kg DM) faba bean seeds (dried and milled prior to feeding) at inclusion levels of 260, 403, and 546 g/kg. Analyzed P content ranged from 2.37 to 4.09 g/kg DM in raw faba bean feeds and 2.64 to 4.41 g/kg DM in crimped-ensiled faba bean feeds. Dietary InsP6 content increased from 2.51 to 5.02 and 5.08 g/kg DM in raw and crimped-ensiled faba bean feeds, respectively. On d 28 post-hatch, all birds were sacrificed, and digesta samples were collected from the distal ileum. Increasing faba bean seed inclusion in feeds linearly decreased the pre-cecal disappearance of InsP6 in broiler chickens (p < 0.01) and values were lower in birds fed crimped-ensiled faba bean seeds (36.8 vs. 46.0 %). Irrespective of the processing method, faba bean inclusion linearly decreased the apparent pcd of P of feeds (p < 0.01), but birds fed crimped-ensiled beans showed higher pcd of P (p < 0.01) compared to those fed raw seeds (72.1 vs. 61.3 %). The pcd coefficients of P for raw and dried crimped-ensiled faba bean seeds (cv. Vire) were 42 % and 49 %, respectively. Increasing faba bean inclusion and dietary P concentration improved performance responses (p < 0.01), and broilers fed crimped-ensiled faba beans exhibited better performance compared to birds fed raw seeds (p < 0.01). The crimping-ensiling process increased the pre-cecal disappearance of InsP6 and the pcd of P in faba bean seeds when fed to broiler chickens.
Keywords: phytate degradation; phosphorus digestibility; fermentation; leguminous crop